The Mental Scenarios and Internet Genre Etiquette of Different Cultures (Based on Online Greetings in Four Languages) - Lassan, Eleonora (Respectus Philologicus, 2012)
This article analyses online greetings in the Russian, Polish, Lithuanian and German languages. The author treats greetings as a speech act which helps the addresser to remind the addressee of his/her good attitude towards him/her on the basis of a particular occasion—the addressee’s birthday. The author analyses this speech act in relation to the specific communicative and mental scenarios of the culture to which the speaker belongs. The entirety of standard speech acts and the combination of intentions of the speakers form a genre. The genre of modern online greetings seems contiguous to folklore genres, because most of the texts do not have authors. Moreover, these texts move from one Internet site to another, resulting in a wide circle of “implementers”—users.The author distinguishes some typical characteristics of online greetings among the four cultures. An emphasis on the figure of the speaker and an incantatory character are typical of Russian greeting texts. Happiness, health and eternal youth are the key objects of these Russian texts. Russian greetings are related to the future. German greetings are mainly related to the birthday celebration itself. Greetings are often related to a review of life: on this occasion the addressee is encouraged to reflect on whether s/he has lived the past year appropriately. The word courage (Mut) is constantly repeated in German greetings, whereas this word is absent from the Russian greetings. The figure of the speaker is marginally expressed in Polish greetings. The sweetness of life is present in Polish greetings, whereas it is observed neither in German nor in Russian texts. May all your dreams come true is a cliché element of Polish greeting texts. Lithuanian greetings distinguish themselves by their melancholic tone.The author relates the detected specific features of online greetings to the ideas of philosophers and historians on the unique means of expressing one’s national character.
Keywords: online greetings; folklore; genre; composition; cultural scenarios; key conceptions